Faktor-Faktor Yang Memengaruhi Struktur Modal - Cindy Andriani, Liana Susanto (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to analyze and obtain empirical evidence regarding the effect of liquidity, profitability, firm size, leverage operation, and sales growth on capital structure on companies listed on the Indonesia Stock Exchange during the periode of 2017-2019. This research was conducted by taking 37 samples of companies, using purposive sampling technique and processed using Eviews version 11. Based on the reseacrh the results show that the liquidity has a negative influence and significant effect on capital structure, while the profitability, firm size, leverage operation and firm size do not have a significant effect on capital structure. The implicationof this research is the impotance of capital structure which aims to finance operations and company expansion.